On-surface stereochemical characterization of a highly curved chiral nanographene by noncontact atomic force microscopy and scanning tunneling microscopy - Zhong, Qigang (2024)
A highly distorted chiral nanographene structure composed of triple corannulene-fused [5]helicenes is prepared with the help of the Heck reaction and oxidative photocyclization with an overall isolated yield of 28%. The complex three-dimensional (3D) structure of the bowl-helix hybrid nanostructure is studied by a combination of noncontact atomic force microscopy (AFM) and scanning tunneling microscopy (STM) on the Cu(111) surface, density functional theory calculations, AFM/STM simulations, and high-performance liquid chromatography-electronic circular dichroism analysis. This examination reveals a molecular structure in which the three bowl-shaped corannulene bladesd position themselves in a C3-symmetric fashion around a highly twisted triphenylene core. The molecule appears to be shaped like a propeller in which the concave side of the bowls face away from the connected [5]helicene motif. The chirality of the nanostructure is confirmed by the direct visualization of both MMM and PPP enantiomers at the single-molecule level by scanning probe microscopies. These results underline that submolecular resolution imaging by AFM/STM is a powerful real-space tool for the stereochemical characterization of 3D curved chiral nanographene structures.